STYLISTIC DEVIATION IN THE SELECTED LITERARY WORKS OF KRISTIAN CORDERO - Mae N. Elamera, Erica; Arah O. Sales, Princess; B. Slleza, Kpecjoe (SIGEH ELT : Journal of Literature and Linguistics, 2023)
This study conducted a stylistic analysis focusing on the deviations in the five (5) Bikol poems of Kristian Cordero, an acclaimed poet, fiction writer, and filmmaker based in the Bicol region. The term stylistic deviation refers to violating the ordinary use of a language, language structure, and patterns. This aims to identify the distortions in language and discover the theme conveyed by the deviations. The depiction of deviations was done in three levels: lexical, semantic, and phonological. The five (5) poems from Cordero’s book "Santigwar" were chosen through random sampling using the fishbowl draw technique and extensively interpreted and analyzed by the researchers, who employed documentary analysis and a closed reading method. Documentary analysis is a type of qualitative research in which researchers evaluate and examine documents or literary works in great detail to give meaning to the text. A closed readingtechnique looked at how a text's language and style are used. This analysis aids in comprehending the deviations and how these deviations reinforced poetic theme. The findings and discussion of this study show how Kristian Cordero employed a stylistic method to express themes figuratively. The study reveals that the three style deviations are present and working constructively. Thus, the reader will better understand the poem's stylistic qualities.